2013
DOI: 10.13157/arla.60.2.2013.437
|View full text |Cite
|
Sign up to set email alerts
|

Observaciones De Aves Raras En España, 2011

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
5
0
2
Order By: Relevance
“…Although the northward expansion of the species' range is short in terms of distance, it is a large step in biogeographical terms. There has been a recent increase in the geographical distribution of observations, with records further north in Spain (Guti errez et al 2012(Guti errez et al , 2013 This bird illustrates the fact that species distributions are not fixed. Thomas et al (2001) demonstrated that, even in the short term, climate may modify species distributions at their margins.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…Although the northward expansion of the species' range is short in terms of distance, it is a large step in biogeographical terms. There has been a recent increase in the geographical distribution of observations, with records further north in Spain (Guti errez et al 2012(Guti errez et al , 2013 This bird illustrates the fact that species distributions are not fixed. Thomas et al (2001) demonstrated that, even in the short term, climate may modify species distributions at their margins.…”
mentioning
confidence: 84%
“…, , Gutiérrez et al . , ). In 2004, the African Long‐legged Buzzard nested in Ceuta (Muñoz , Ávila et al .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In both cases the first records have occurred in the same geographical area (the Gibraltar Strait) and during similar periods -the end of summer and early autumn (Jara et al 2008, Dies et al 2011, Gutiérrez et al 2013. In this context, another raptor species, the North African Long-Legged Buzzard (Buteo rufinus cirtensis), had a similar process in the past and has been recently recorded breeding in the Gibraltar Strait area in southern Spain (Elorriaga & Muñoz, 2010).…”
mentioning
confidence: 94%
“…Se homologan cinco nuevos registros que siguen el patrón usual de esta especie (todos excepto uno, en el estrecho de Gibraltar). Uno de los individuos muestra rasgos típicos de los híbridos con Ardeola 64 (1), 2017, 161-235 ratonero común Buteo rufinus × buteo que se registran con cierta frecuencia en el entorno del Estrecho (Rodríguez et al, 2013). Los otros inviduos no presentan rasgos que sugieran hibridación y parecen pertenecer a la subespecie norteafricana cirtensis.…”
Section: Busardo Morounclassified